Factors associated with edentulousness in an elderly population in Valencia (Spain) Factores asociados con el edentulismo en población anciana de Valencia (España) - María Vicenta Eustaquio-Raga; José María Montiel-Company; José Manuel Almerich-Silla (Elsevier, 2013)
Objective: To determine the prevalence of edentulism and its association with various socioeconomic factors and oral health habits in the population aged 65-74 years old in the region of Valencia. Methods: A cross sectional study was designed. Thirty-four primary health centers and five nursing homes were chosen at random in the region of Valencia (10-15 voluntary participants per sampling point). Clinical examinations were carried out by three calibrated dentists (kappa>0.85) in the same centers. The total sample consisted of 531 individuals (235 men and 296 women). Results: The percentage of toothlessness was 20.7% and the mean number of natural teeth present was 14.92. The prevalence of edentulism was significantly higher (p <0.05) in men, institutionalized persons, those with no schooling, those with poor oral hygiene, those who visited the dentist regularly and those living in peri-urban/rural areas. In a multivariate logistic regression model with edentulism as the dependent variable, the following factors were identified as significant independent variables: institutionalization (odds ratio [OR]=2.88), poor oral hygiene (OR=2.35), regular visits to the dentist (OR=2.34) and age (OR=1.19). Conclusion: Edentulousness is a complex phenomenon that involves distinct social and economic factors. Objetivo: Determinar la prevalencia del edentulismo y su asociación con diferentes factores socioeconómicos y de hábitos de salud oral en la población valenciana de 65 a 74 años de edad. Métodos: Se diseñó un estudio transversal. Se seleccionaron aleatoriamente 34 centros de salud de atención primaria y cinco residencias geriátricas de la Comunidad Valenciana (10 a 15 individuos voluntarios por punto de muestreo). Las exploraciones clínicas las realizaron tres odontólogos previamente calibrados (kappa>0.85) en los mismos centros. La muestra total fue de 531 personas, 235 hombres y 296 mujeres. Resultados: El porcentaje de desdentados totales fue de 20,7, y la media de dientes naturales presente de 14,92. La prevalencia de edentulismo fue significativamente mayor (p <0.05) en los hombres, en las personas institucionalizadas, que no tienen estudios, con pobre higiene oral, que visitan regularmente al odontólogo y en las que viven en zonas periurbanas o rurales. En un modelo de regresión logística multivariada con el edentulismo como variable dependiente se han hallado como variables significativas la institucionalización (odds ratio [OR]=2,88), la pobre higiene oral (OR=2,35), las visitas regulares al odontólogo (OR=2,34) y la edad (OR=1,19). Conclusión: El edentulismo es un fenómeno complejo, con diversos factores sociales y económicos implicados.